Challenging the Minimum Effective Antipsychotic Dose During Maintenance: Implications From 10-Year Follow-Up of First Episode Psychosis - Liu, Chen-Chung; Liu, Chih-Min; Chien, Yi-Ling; Lin, Yi-Ting; Hsieh, Ming H.; Hwang, Tzung-Jeng; Hwu, Hai-Gwo (Frontiers in Psychiatry, 2021)
Background: Contradictory messages regarding the necessity of long-term antipsychotic treatment after first episode psychosis arouse deliberations in clinical practice. We explored if there is an alternative beyond the dichotomy of maintenance treatment and discontinuation of medications. Methods: We conducted a retrospective observational study by reviewing medical records at the study hospital of a cohort of patients since their participation in an early psychosis study starting from 2006, with special interests in patients able to maintain good functioning under treatment with a low antipsychotic dose. Results: Of the 81 patients with first episode psychosis, 55 patients (67.9%) had follow-up information for longer than 5 years. The majority (n=46, 83.6%) had non-affective psychosis, 20 patients (36.4%) had full-time employment/education by the time of their latest visit; among them 15 patients received dosage of antipsychotics no more than the minimum effective dose (chlorpromazine equivalent [CPZE] dose 200 mg/d). Besides, 10 of 55 patients (18.2%) only received very low dose antipsychotics (CPZE < 50 mg/d) during maintenance, which was significantly correlated to good functioning. Being male, having a history of hospitalization and being on clozapine therapy were correlated to poorer functioning. Antipsychotic-free status was achieved only in two non-psychotic patients. Conclusions: A substantial proportion of patients could achieve good functioning under low-dose antipsychotic maintenance after first episode psychosis, even if they could not completely withdraw antipsychotics in the long term. Optimizing the balance between preventing relapse and preserving functioning by fine-tuning antipsychotic dosage during maintenance is a challenge warranting more clinical attention